Implementation of High Speed Vedic Multiplier Using Vertical and Crosswise Algorithm - G. Vadiraj; K. Shivanand; B. Sampat; G. Subramanya Nayak (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
Multiplication is an important fundamental function in arithmetic operations. Multiplication-based operations such as Multiply and Accumulate (MAC) and inner product are some of the frequently used operations in many Digital Signal Processing (DSP) applications such as convolution, Fast Fourier Transform(FFT), filtering and in microprocessors in its arithmetic and logic unit. Since multiplication dominates the execution time of most DSP algorithms, so there is a need of high speed multiplier. Higher throughput arithmetic operations are important to achieve the desired performance in many real-time signal and image processing applications. In this project, the comparative study of Vedic multiplier and Sequential multiplier is done for low power requirement and high speed. The proposed architecture is based on the Vertical and Crosswise algorithm of ancient Indian Vedic Mathematics, which increases the speed of multiplier by reducing the number of clock cycles thus achieving the greater speed of the processor or system.